Western immunoblot analysis and serologic characterization of Blastomyces dermatitidis yeast form extracellular antigens. - Hurst, S F (1992)
A major 98-kDa extracellular protein antigen of Blastomyces dermatitidis was shown in Western blot (immunoblot) analysis to be highly reactive with serum antibodies from patients with blastomycosis. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis of yeast form B. dermatitidis culture filtrates and cell extracts demonstrated over 50 proteins, only 24 of which were immunoreactive. Of these, a 98-kDa protein was found to be the most specific and was isolated. This protein was found in both broth culture filtrates and extracts of yeast forms. Western blot tests with this antigen detected serum antibodies in 91% of 32 patients with clinically proven blastomycosis, in contrast to an enzyme-linked immunosorbent assay (ELISA) with DEAE-purified antigen, which detected 88% of the cases. The Western blot test also exhibited lower reactivity with a panel of sera from patients with heterologous fungal infections that were cross-reactive in the ELISA with DEAE-purified B. dermatitidis antigen. The 98-kDa protein electroeluted from polyacrylamide gels was identical to the diagnostic A antigen used in the blastomycosis immunodiffusion test. Comparison of the 98-kDa antigen with a previously described 120-kDa yeast form cell wall protein antigen of B. dermatitidis showed that these two antigens are almost identical.